Short Term Effects of Inner Engineering Completion Online Program on Stress and Well-Being Measures - Upadhyay, Preeti; Joshi, Akshaj; Mishra, Isha; Kelly, Lauren; Novack, Lena; Hariri, Sepideh; Kveraga, Kestutis; Subramaniam, Balachundhar (Frontiers in Psychology, 2022)
Introduction: The Covid-19 pandemic has been a major disruptor of routine life, resulting in increased stress and predisposing people to negative outcomes, such as insomnia, anxiety and hopelessness. Mind-body interventions have improved concentration, emotional balance, and positive emotions, with an enhanced sense of productivity, and self-confidence. We therefore hypothesized that exposure to an online mind-body intervention, ‘Inner Engineering Completion Online’, would reduce stress and promote wellbeing. Methods: This prospective cohort study enrolled participants registered for the Inner Engineering Completion Online (IECO) courses, which for the first time were delivered remotely, online. Participants learned a 21-minute meditation practice called Shambhavi Mahamudra Kriya during the course, which incorporates controlled breathing & mediation techniques. Each enrolled participant was asked to complete self-reported electronic surveys at three key time points: at the time of consent, immediately after completing IECO, and six weeks after IECO completion. Effects of IECO practice were assessed using four well-validated neuropsychological scales: Perceived Stress Score (PSS), PERMA Profiler, Pittsburgh Sleep Quality Index (PSQI), and Mindful Attention Awareness Scale (MAAS). A Signed Rank test was used to analyze the survey data and P values of <0.05 were considered statistically significant. Results: Of the 375 participants interested in participation, 164 participants were eligible. Sixty-eight participants completed surveys at all time points and were identified as compliant participants. The baseline median score for perceived stress score (PSS) in compliant participants was 13 (IQR 9, 18); immediate post-IECO median PSS score was 11.5 (IQR 8, 16) demonstrating a 1.5 unit decrease in PSS scores (p-value = 0.0023). Similarly, comparing PSS scores for immediate Post IECO [11.5 (IQR 8, 15.5)] to PSS scores at six weeks [8 (IQR 4.5, 12.5)] showed a statistically significant 3.5-unit decrease, indicating a reduction in stress upon routine practice of the intervention (p<0.0001). Figure 1: Time trend comparison of PSS Scores in compliant participants. Conclusion: Incorporating the remotely delivered mind-body intervention Shambhavi Mahamudra Kriya into daily life via the IECO program over as few as six weeks produced a significant stress reduction, improvement in sleep quality & mindfulness.